2014
DOI: 10.1128/jvi.01678-14
|View full text |Cite
|
Sign up to set email alerts
|

Stearoyl Coenzyme A Desaturase 1 Is Associated with Hepatitis C Virus Replication Complex and Regulates Viral Replication

Abstract: The hepatitis C virus (HCV) life cycle is tightly regulated by lipid metabolism of host cells. In order to identify host factors involved in HCV propagation, we have recently screened a small interfering RNA (siRNA) library targeting host genes that control lipid metabolism and lipid droplet formation using cell culture-grown HCV (HCVcc)-infected cells. We selected and characterized the gene encoding stearoyl coenzyme A (CoA) desaturase 1 (SCD1). siRNA-mediated knockdown or pharmacological inhibition of SCD1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 49 publications
(57 reference statements)
2
40
0
Order By: Relevance
“…Phospholipid acyl chain saturation has been implicated in genome replication and virion infectivity of RNA and DNA viruses (11,12). Pharmacological inhibition of stearoyl-coenzyme A desaturase (SCD-1), an enzyme that converts saturated to unsaturated acyl chains, was recently shown to suppress HCV replication and hence proposed to be a potential antiviral strategy (58,59). Likewise, in light of our findings, decreasing the levels of PI(4,5)P 2 with unsaturated acyl chains by using a similar strategy may abrogate Gag membrane binding and/or proper Gag localization with minimal effects on cellular PI(4,5)P 2 -dependent processes.…”
Section: Figmentioning
confidence: 99%
“…Phospholipid acyl chain saturation has been implicated in genome replication and virion infectivity of RNA and DNA viruses (11,12). Pharmacological inhibition of stearoyl-coenzyme A desaturase (SCD-1), an enzyme that converts saturated to unsaturated acyl chains, was recently shown to suppress HCV replication and hence proposed to be a potential antiviral strategy (58,59). Likewise, in light of our findings, decreasing the levels of PI(4,5)P 2 with unsaturated acyl chains by using a similar strategy may abrogate Gag membrane binding and/or proper Gag localization with minimal effects on cellular PI(4,5)P 2 -dependent processes.…”
Section: Figmentioning
confidence: 99%
“…We next asked if Pim kinases are involved in HCV internal ribosome entry site (IRES)-mediated translation. To address this question, Huh7.5 cells were treated with various concentrations of SGI-1776 and then transfected with pRL-HL and ␤-galactosidase plasmid as we reported previously (19), and then luciferase activity was determined. We demonstrated that treatment of Pim kinase inhibitor displayed no effects on HCV IRES-dependent translation (Fig.…”
Section: Identification Of Pim1 As An Ns5a Interactor In Protein Arraymentioning
confidence: 99%
“…For the dual-luciferase reporter assay, Huh7.5 cells were transfected with pRL-HL plasmid and pCH110 reference plasmid as we described previously (19). The cells were then incubated with various dosages of Pim kinase inhibitor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…TRIB3 promoter constructs (from bp Ϫ2000 to ϩ558) were cloned by using Huh7 genomic DNA and inserted into the pGL3 Basic vector (Promega). Myc-tagged HCV core, NS3, NS4B, NS5A, and NS5B plasmids were described previously (11). For DNA transfection, cells were transfected with the expression plasmid by using a polyethyleneimine reagent (Sigma-Aldrich) as we described previously (11).…”
Section: Methodsmentioning
confidence: 99%